Vegetation, rainfall, and pulsing hydrology in the Pantanal, the world’s largest tropical wetland - Sarah J Ivory; Michael M McGlue; Stephanie Spera; Aguinaldo Silva; Ivan Bergier (Environmental Research Letters, 2019)
Wetlands provide valuable ecosystem services and play a central role in global carbon cycling. Changes in rainfall and the flood-pulse are likely to disrupt the processes that maintain these landscapes; further, landscape modification may dramatically alter wetlands and promote terrestrialization. The Pantanal, South America, is the world’s largest wetland due to flooding along the Upper Paraguay River. Predicting how water resources in the Pantanal may change is problematic due to a complex drainage network, resulting in the out-of-phase timing of rainfall and the flood pulse. We use remote sensing data of vegetation and climate to better understand the relationships among the rains, the flood pulse, and vegetation. Although rainfall is regionally synchronous, vegetation responses differ based on position relative to inundated areas. Away from rivers, vegetation greening occurs immediately following rainfall. Along channels, greening may lag rainfall by six months, responding closely to local flood stage. Interannual rainfall variability also impacts vegetation differently near flooded areas, with weaker, lagged responses to rainfall due to local water storage. This work suggests that the importance of flood pulse timing for vegetation productivity in inundated areas means that local conditions in wetlands may be the strongest controls on biogeochemical processes.